Landmines and human security : international politics and war's hidden legacy - Matthew, Richard A., 1959-; McDonald, Bryan (Bryan L.); Rutherford, Ken, 1962- (Albany : State University of New York Press, 2004)
"An impressive array of activists, scholars, government officials, journalists, and landmine victims themselves are gathered here to tell the story of the International Campaign to Ban Landmines (ICBL). Organized in the early 1990s, the ICBL is a network of more than one thousand nongovernmental organizations worldwide, working for a global ban on landmines. It was an important force behind the treaty to ban antipersonnel landmines that was signed in Ottawa in 1997, and which led to its being awarded the 1997 Nobel Peace Prize, along with its coordinator."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved
Environmental impacts of landmines / Claudio Torres Nachón -- Necessary evil? : reexamining the military utility of antipersonnel landmines / Ted Gaulin -- Are landmines still needed to defend South Korea? : a mine use case study / J. Antonio Ohe -- Campaign to ban antipersonnel landmines : potential lessons / Stephen Goose, Jody Williams -- Campaign to ban antipersonnel landmines and global civil society / Paul Wapner -- Human security and the mine ban movement II : conclusions / Richard A. Matthew.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Übereinkommen über das Verbot des Einsatzes, der Lagerung, der Herstellung und der Weitergabe von Antipersonenminen und über deren Vernichtung; Convention sur les mines antipersonnel; Land mines (International law); Arms control -- International cooperation; Land mine victims; Mines individuelles (Droit international); Armements -- Contrôle -- Coopération internationale; Victimes de mines individuelles; POLITICAL SCIENCE -- International Relations -- Arms Control; Arms control -- International cooperation; Land mine victims; Land mines (International law); Abrüstung; Abrüstungsinitiative; Antipersonenmine; Internationale Politik; Kriegsopfer; Landmine; Nichtstaatliche Organisation; Mijnen (wapens); Ontwapening; Politieke bewegingen; Hulpverlening; Mines; Arms control; International co-operation.; War victims; Convention on the Prohibition of the Use, Stockpiling, Production and Transfer of Anti-Personnel Mines and on Their Destruction [Ottawa, 3 December 1997].; Campagne d'information.; Coopération internationale; Limitation des armements; Mine antipersonnel; Politique internationale